Postoperative arginine-enriched immune modulating nutrition: Long-term survival results from a randomised clinical trial in patients with oesophagogastric and pancreaticobiliary cancer. Issue 11 (November 2021) - Adiamah, Alfred; Rollins, Katie E.; Kapeleris, Audrey; Welch, Neil T.; Iftikhar, Syed Y.; Allison, Simon P.; Lobo, Dileep N.
Summary: Background & aims: Immune modulating nutrition (IMN) has been shown to reduce postoperative infectious complications and length of stay in patients with gastrointestinal cancer. Two studies of IMN in patients undergoing surgery for head and neck cancer also suggested that this treatment might improve long-term survival and progression-free survival. In the present study, we analysed follow-up data from our previous randomised controlled trial of IMN, in patients undergoing surgery for oesophagogastric and pancreaticobiliary cancer, in order to evaluate the long-term impact on survival of postoperative IMN versus an isocaloric, isonitrogenous control feed. Methods: This study included patients undergoing surgery for cancers of the pancreas, oesophagus and stomach, who had been randomised in a double-blind manner to receive postoperative jejunostomy feeding with IMN (Stresson, Nutricia Ltd.) or an isonitrogenous, isocaloric feed (Nutrison High Protein, Nutricia) for 10–15 days. The primary outcome was long-term overall survival. Results: There was complete follow-up for all 108 patients, with 54 patients randomised to each group. There were no statistically significant differences between groups by demographics [(age, p = 0.63), sex (p = 0.49) or site of cancer (p = 0.25)]. 30-day mortality was 11.1% in both groups. Mortality in the intervention group was 13%, 31.5%, 70.4%, 85.2%, 88.9%, and 96.3% at 90 days, and 1, 5, 10, 15 and 20 years respectively. Corresponding mortality in the control group was 14.8%, 35.2%, 68.6%, 79.6%, 85.2% and 98.1% (p > 0.05 for all comparisons). Conclusion: Early postoperative feeding with arginine-enriched IMN had no impact on long-term survival in patients undergoing surgery for oesophagogastric and pancreaticobiliary cancer.